Storyworlds: little red riding hood - Andrew, Moira (Heinemann UK, 2009)
*Little Red Riding Hood* is a classic fairy tale about a young girl who sets off to visit her grandmother, wearing a red cloak. Along the way, she meets a cunning wolf who tricks her into revealing the location of her grandmother's house. The wolf arrives first, disguises himself as the grandmother, and tries to deceive Little Red Riding Hood, but with the help of a woodcutter, she is saved and learns an important lesson about being cautious with strangers.